Intramolecular Chloro–Sulfur Interaction and Asymmetric Side‐Chain Isomerization to Balance Crystallinity and Miscibility in All‐Small‐Molecule Solar Cells. (11th July 2022) - Gao, Wei; Jiang, Mengyun; Wu, Ziang; Fan, Baobing; Jiang, Wenlin; Cai, Ning; Xie, Hua; Lin, Francis R.; Luo, Jingdong; An, Qiaoshi; Woo, Han Young; Jen, Alex K.‐Y.
Abstract: Intramolecular Cl−S non‐covalent interaction is introduced to modify molecular backbone of a benzodithiophene terthiophene rhodamine (BTR) benchmark structure, helping planarize and rigidify the molecular framework for improving charge transport. Theoretical simulations and temperature‐variable NMR experiments clearly validate the existence of Cl−S non‐covalent interaction in two designed chlorinated donors and explain its important role in enhancing planarity and rigidity of the molecules for enhancing their crystallinity. The asymmetric isomerization of side‐chains further optimizes the molecular orientation and surface energy to strike a balance between its crystallinity and miscibility. This carefully manipulated molecular design helps result in increased carrier mobility and suppressed charge recombination to obtain simultaneously enhanced short‐circuit current ( J sc ) and fill factor (FF) and a very high efficiency of 15.73 % in binary all‐small‐molecule organic solar cells. Abstract : Introduction of Cl atoms into the backbone in small‐molecule donors (SMDs) enhances the molecular planarity and rigidity through intramolecular Cl−S interactions. Additionally, asymmetric isomerization of side chains balances crystallinity and miscibility to achieve ideal morphology for simultaneously high short‐circuit current density and fill factor to yield a record power conversion efficiency of 15.73 % among halogenated SMD‐based binary all‐small‐molecule organic solar cells.